Construção e validação de instrumento para avaliar o conhecimento dos pais sobre alimentação complementar do lactente - Oliveira, Edcarla da Silva (2017)
The supplementary feeding of children under two years of age in our society is shown in several studies, less than that recommended by the Ministry of Health and the World Health Organization, with frequent consumption of cow's milk, flour, chocolate, sugars, snacks, candy It is necessary to evaluate parents' knowledge about their children's diet, because there are cultural, social, economic and psychosocial factors that have a great impact on the establishment of eating habits in childhood. The aim of this study was to validate an evaluative questionnaire about parents '/ caregivers' knowledge about complementary feeding of infants. It was a methodological and developmental study, for the construction and validation of the face and content of an instrument on complementary feeding of infants (children between 6 months and 2 years old) directed to parents. The built material was appreciated by professionals with expertise in the field. For the construction of the instrument was followed the theoretical reference of Pasquali, the Psychometry. Six expert judges were selected through the Lattes Platform of the National Council for Scientific and Technological Development (CNPq). After evaluating the judges, the requested adjustments were made and the instrument was again sent to the final assessment. The data of the research were stored in database for analysis and calculation of Content Validity Index (IVC) after the evaluation of the experts, to determine the level of agreement between them. The IVC of 0.80 was used as the standard for establishing excellence in the content validity of the instrument. The research was approved by the Ethics and Research Committee of the Federal University of Ceará, with an opinion under No. 1,974,942. The first version of the questionnaire was composed of 44 questions. After the validation stage, changes related to the items clear introduction, food preparation, family importance in food and clarity of information were performed, as they obtained IVCi <0.60. Four questions were deleted (paragraphs 6, 18, 20 and 37). The questionnaire was again sent to the judges, undergoing new changes in the four domains, excluding five questions (no. 6, 8, 12, 16 and 33), with the final version of 35 questions. The respondent has three options for answering the questions: I agree, disagree and agree in part, and the item marked as part agree has space for comments. The instrument was divided into four areas: introduction and complementary feeding, complementary types of food, food and hygiene in the preparation of food and utensils. The individually evaluated items were considered adequate with IVC ≥ 0.80, demonstrating contents pertinent to the complementary evaluation. About the overall evaluation the content was considered valid with IVC of 0.83 after modifications. Thus, the questionnaire to evaluate parents' knowledge about infant complementary feeding was considered a technology with valid content to be used in nursing environments from Basic Health Units to schools. It was concluded that, with the questionnaire, the nurse can contribute to the improvement of the health promotion of the child in the food context. However, it needs to be evaluated with other types of validation so that it can be used in clinical practice.